Proline biosynthesizing enzymes (glutamate 5-kinase and pyrroline-5-carboxylate reductase) from a model cyanobacterium for desiccation tolerance - Singh, Priyanka (Springer India, 2013)
Drought is the most important abiotic stress, challenging sustainable agriculture globally. For desiccation being the multigenic trait, a combination of identified genes from the appropriate organism may render crop tolerant to the water stress. Among the compatible solutes, proline plays multifaceted role in counteracting such stress. The genes encoding proline biosynthesizing enzymes, glutamate 5-kinase (G5K), and pyrroline-5-carboxylate reductase (P5CR) from the low-desiccation-tolerant cyanobacterium Anabaena sp. PCC 7120, were cloned and overexpressed in Escherichia coli BL21(DE3) individually. The recombinant E. coli cells harboring G5K, failed to exhibit enhanced desiccation tolerance relative to those with P5CR that showed increased growth/survival over the wild type. This may be ascribed to the overexpression of the reductase gene. Multiple sequence alignment showed P5CR to be conserved in all the organisms. We hypothesize that P5CR gene from high-desiccation-tolerant cyanobacteria may be adopted as the candidate for making transgenic N(2)-fixing cyanobacterium for paddy fields and/or crop development in future.